Solid acid catalysts for sustainable production of biodiesel - Zhang, Honglei (2016)
Homogeneous acid catalysts, such as H2SO4, are playing significant roles in catalytic processes for the manufacture of a wide range of important chemicals such as pharmaceuticals, petrochemicals, and fragrances. However, the use of liquid acid catalysts is normally associated with engineering problems, such as the difficulty in its separation from products, the formation of large quantity of wastewater and corrosion to the equipment. Consequently, it is desirable to develop highly active, inexpensive, green and reusable heterogeneous acid catalysts for various applications. To date, the R&D of heterogeneous solid acid catalysts has become a forefront of scientific research and attracted worldwide attentions. The aim of this work is to develop novel heterogeneous catalysts that can be used to replace homogeneous catalysts in the esterification of free fatty acid with methanol for biodiesel production. Three types of heterogeneous solid acid catalysts, i.e., sulfonated cation-ion exchange resin (s-CER)/polyvinyl alcohol (PVA) catalytic membranes, sulfur-rich graphene oxide catalysts, and sulfonated hydrothermal carbon microspheres (S-HTC), were prepared in this study. These solid acid catalysts were systematically characterized by using techniques, such as Field Emission Scanning Electron Microscope (FESEM), Transmission Electron Microscope (TEM), X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Raman, X-Ray Photoelectron Spectroscopy (XPS), Elemental analyzer (EA), Energy Dispersive X-Ray Spectroscopy (EDX), nitrogen adsorption, acid-base titration, and Thermogravimetric Analyzer - Differential Scanning Calorimeter (TGA-DSC), to show chemical and physical properties of the catalysts. Results of these characterisations were then used to study the relationship between the catalytic activities of the solid acidic catalysts and their physical and chemical properties. Sulfonated-cation exchange resin (S-CER)/Polyvinyl alcohol (PVA) catalytic membrane has been studied in the esterification under a free fatty acids of 20 g, methanol/FFAs mass ratio of 2.5:1 (equivalent to molar ratio 29:1); a catalytic membrane loading of 4 g; a mechanical stirring rate of 360 rpm; reaction temperature of 338 K; and a reaction time of 8 h. Sulfonated cation exchange resins (s-CER) have been widely studied for the catalysis of esterification of FFAs to produce biodiesel with water as the only by-product. However, the water produced has strong affinity to sulfonate groups in s-CER, which blocks the reactive sites for esterification and thus reduces the activity of the s-CER. PVA has much stronger absorption preference of water than s-CER and has very low selectivity for the reactants (FFAs and methanol), which enables the continuous removal of the produced water and liberation of the reactive sulfonate sites in s-CER for catalysis. The catalytic activity of the membrane was compared with that of sulfuric acid and s-CER alone. With s-CER/PVA as the catalyst, the FFAs conversion increased from 80.1 % to 97.5 % after 8 hours’ reaction. The turnover frequency (TOF) increased by more than 3.3 times. The TOF of s-CER/ PVA were also 2.6 times higher than that of sulfuric acid. The reusability of the s-CER/PVA was also enhanced because the water yielded was largely removed by the PVA. Moreover, this catalyst has high reusability at moderate reaction temperatures with no need of catalyst re-treatment during the reuse process. The reaction mechanism for the esterification catalyzed by the s-CER/PVA was also studied. It was found that the PVA played two major roles in the esterification process, supporting the catalyst for separation and reutilization; liberating the –SO3H sites for esterification by adsorbing the water yielded and promoting the forward reaction. Different types of sulfur-rich graphene oxide (GO-S) catalysts were prepared and tested in the esterification of oleic acid with methanol. Catalytic activity of the GO-S was compared with sulfuric acid, two other GO samples and nine carbon-based solid acid catalysts prepared using other methods. The GO-S showed the highest catalytic activity and reusability. The TOF of the GO-S was about 3 times higher than that of the sulfuric acid. There are two key properties leading to the high catalytic performance: 1) the 2-D layered structure which allows reactants enter the internal space of the GO-S and access the catalytic active sites easily; and 2) the synergic effect between the surface –SO3H and –COOH groups. A GO/PES catalytic membrane was also prepared by immersion phase inversion method and employed in the esterification of oleic acid with methanol for biodiesel production. The reaction conditions were studied and determined to be: GO/ PES mass ratio 1:5, membrane annealing temperature 150 °C, membrane thickness 0.1 mm, membrane dimension 0.5 cm ×0.5 cm, catalytic membrane 4 g, reaction temperature of 65 °C, and the methanol/oleic acid mass ratio 2.0:1. The sulfonated hydrothermal carbon microspheric (S-HTC) material was also employed in the esterification of oleic acid with methanol. The reaction conditions were studied comprehensively to achieve the optimal yield of biodiesel under minimized production cost. The catalyst showed fairly high catalytic performance with a high yield of 92 % under the optimal reaction conditions: a methanol/oleic acid molar ratio of 12:1, a catalyst loading of 0.25 g, a reaction temperature of 65 °C, a reaction time of 8 hours and a mechanical stirring rate of 360 rpm. The S-HTC also showed very good catalytic recyclability with a yield of approximate 84 % after five runs. Future work will be done to test the catalytic performance in commercial large-scale production of biodiesel. Several works are needed to solve the problem that GO-S and S-HTC are hard to be recycled from the reaction mixtures.